Recapitalization of one class of common stock into dual-class: Growth and long-run stock returns - Dimitrov, Valentin; Jain, Prem C. (Journal of Corporate Finance, 2006)
We study a sample of 178 firms that changed from a one-share one-vote into a dual-class common stock structure during 1979–1998. We find that dual-class recapitalizations are shareholder value enhancing corporate initiatives. Using accounting data, Lehn et al. (1990) [Lehn, K., Netter, J., Poulsen, A., 1990. Consolidating corporate control: dual-class recapitalizations versus leveraged buyouts. Journal of Financial Economics 27, 557–580] provide evidence that dual-class recapitalizing firms grow faster than firms in a control group and undertake secondary equity offerings (SEOs) to finance growth. We show that growth is indeed beneficial to the shareholders. The stockholders, on average, earn significant positive abnormal returns of 23.11% in a period of 4 years following the announcement month. Furthermore, abnormal returns are even larger (52.61%) for the dual-class firms that issue equity. This evidence is especially supportive of the value enhancing hypothesis as it is contrary to the prevailing result that SEOs are generally followed by large negative returns. We do not find any evidence of managerial entrenchment.